The South African e‐Retail Change Agenda: A Curriculum Development Perspective. Issue 1 (5th December 2017) - Alexander, Bennett; Mason, Roger
Abstract: This study provides a broad overview of e‐Retail implementation and its impact on skills development within the South African retail sector. The study interrogates the readiness of the South African retail sector for e‐Retail on the basis of a selection of technology, marketing, operations and business imperatives; and provides in particular a predictive analysis of the technical skills requirement to sustain a viable e‐Retail industry in the country. In this regard, a set of salient e‐Retail functions, skills and services are identified that pragmatically define a set of baseline competencies for implementation. Furthermore, a proposed framework for a professional qualification in e‐Retail Management is provided as a possible Higher Education curriculum intervention. The study deploys a Design Science Research approach that informs the design and construction of various knowledge artefacts that describe the South African e‐Retail experience and aspirations by highlighting salient aspects relating to (1) traditional versus e‐Retail, (2) global e‐Retail trends, (3) e‐Retail technologies and platforms, and (4) e‐Retail training imperatives. The research furthermore elucidates the environment for e‐Retail deployment in South Africa with respect to e‐Retail functions, services and job skills requirements and prospects of e‐Retail as a career. The research methodology deployed in the study centres around the establishment of a change agenda for e‐Retail within the South African landscape. The study identified a comprehensive suite of key and breaking technologies that inform the successful implementation of e‐Retail in South Africa. The study also uncovered essential business process elements that are required to drive the change agenda for e‐Retail in South Africa. In this regards the study draws from salient international case studies as well as relevant national case studies. The study makes significant knowledge contributions with respect to the delineation of salient issues to be addressed with regard to the practical implementation of e‐Retail in South Africa. The study makes a novel methodological contribution by deploying a Design Science approach to establish the process logic for the research and a Critical Interpretivist approach of information synthesis. This strategy allowed the research to be both suggestive of, and receptive to, opportunities and challenges within a complex environment of change and transformation. However, the nature and limitations of the data gathering process places a practical limitation on the value of the research in that generalised conclusions are not possible and information is relevant only for the purpose and within the context that it was mined.